2010
DOI: 10.5551/jat.3202
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Gamma-Glutamyltransferase and Alcohol Drinking with Incident Diabetes: the HIPOP-OHP Study

Abstract: Aim: Gamma-glutamyltransferase (GGT) is known to correlate well with alcohol consumption; however, the relation between GGT and diabetes and that between alcohol consumption and diabetes mellitus (DM) is inconsistent. Thus, several questions, such as whether light to moderate drinkers can be considered as low risk for diabetes incidence irrespective of their GGT level, is unresolved. In this study, we investigated the relation of GGT or alcohol drinking with DM incidence considering the body mass index (BMI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…In addition, some previous studies already showed that higher c-GTP levels were associated with onset of diabetes [41][42][43] and c-GTP increased in patients with nonalcoholic steatohepatitis [44,45]. However, there was no correlation between the serum lactate levels with the serum c-GTP levels in the current study.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, some previous studies already showed that higher c-GTP levels were associated with onset of diabetes [41][42][43] and c-GTP increased in patients with nonalcoholic steatohepatitis [44,45]. However, there was no correlation between the serum lactate levels with the serum c-GTP levels in the current study.…”
Section: Discussioncontrasting
confidence: 77%
“…P<0.05 was taken to be significant. obesity, in a four-year follow-up study 4) , suggesting that GGT may be an independent predictor of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…Several population-based investigations have noted relatively independent cross-sectional and prospective associations between serum GGT levels and certain cardiovascular risk factors [8][9][10][11][12][13][14][15][16] . Most of these studies refer to 'normal' serum GGT levels, which would otherwise raise no specific health concern.…”
Section: Landmark Clinical Trialsmentioning
confidence: 99%
“…The relation of GGT and alcohol drinking with incident DM was recently scrutinized in the HIPOP-OHP Study 15) . A total of 3095 healthy male Japanese workers who did not have DM at baseline were followed for 4 years.…”
Section: Landmark Clinical Trialsmentioning
confidence: 99%